2019
DOI: 10.1007/s11357-019-00054-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of GDF11 on brain fate and function

Abstract: Growth differentiation factor 11 (GDF11) is a transforming growth factor β (TGFβ) protein that regulates aspects of central nervous system (CNS) formation and health throughout the lifespan. During development, GDF11 influences CNS patterning and the genesis, differentiation, maturation, and activity of new cells, which may be primarily dependent on local production and action. In the aged brain, exogenous, peripherally delivered GDF11 may enhance neurogenesis and angiogenesis, as well as improve neuropatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 67 publications
(153 reference statements)
1
20
0
Order By: Relevance
“…Our present findings show a significant decrease in plasma GDF-11 levels in schizophrenia patients, and GDF-11 level was related to the psychopathological symptoms and cognitive impairments. In combination with the roles of GDF-11 in neurogenesis and brain function (15,29,31) and the effects of GDF-11 on nerve development and cell regulations (32)(33)(34), it is indicated that GDF-11 may be related to the pathophysiology of schizophrenia. However, it should be noted that the difference in plasma GDF-11 levels between the patient and control groups could result from schizophrenia itself or other potential influence factors, such as the effect of antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…Our present findings show a significant decrease in plasma GDF-11 levels in schizophrenia patients, and GDF-11 level was related to the psychopathological symptoms and cognitive impairments. In combination with the roles of GDF-11 in neurogenesis and brain function (15,29,31) and the effects of GDF-11 on nerve development and cell regulations (32)(33)(34), it is indicated that GDF-11 may be related to the pathophysiology of schizophrenia. However, it should be noted that the difference in plasma GDF-11 levels between the patient and control groups could result from schizophrenia itself or other potential influence factors, such as the effect of antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other reports argued that GDF11 was positively associated with aging, cachexia, and inhibition of muscle regeneration in aged mice (Egerman et al, ; Harper et al, ; Jones et al, ), while different studies showed a beneficial role for GDF11 in the periphery (Poggioli et al, ; Su et al, ; Walker et al, ). In the central nervous system, GDF11 was also shown to be neuroprotective for neurovascular recovery and neurogenesis (Anqi, Ruiqi, Yanming, & Chao, ; Ma et al, ; Ozek, Krolewski, Buchanan, & Rubin, ; Schafer & LeBrasseur, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Supporting Information Figure S1, the anti‐myostatin antibody was found to bind both myostatin and GDF‐11 with similar affinity. Analogous to myostatin, GDF‐11 functions as a negative regulator of neurogenesis in the developing central nervous system (CNS) . Both proteins share 90% sequence homology, which explains why Domagrozumab can bind to both growth factors.…”
Section: Resultsmentioning
confidence: 99%
“…Analogous to myostatin, GDF-11 functions as a negative regulator of neurogenesis in the developing central nervous system (CNS). 32 Both proteins share 90% sequence homology, which explains why Domagrozumab can bind to both growth factors. As GDF-11 is significantly cheaper than myostatin, this cytokine was chosen for immunoaffinity purification and different amounts were coupled to NHS magnetic sepharose (see 2.3.2).…”
Section: Isolation Of the Target Analyte From Serummentioning
confidence: 99%